Respuesta :

Answer:

m = 5

Step-by-step explanation:

3m - 2 = 13

3m      = 13 + 2

3m      = 15

 m      = 15 :  3

 m      = 5

I hope this answer will help you. Have a nice day !

Answer:

The result for this equation is m = 5.

Step-by-step explanation:

Solve the equation:

[tex]3m -2 =13[/tex]

-Add both sides by 2:

[tex]3m -2 +2 = 13 +2[/tex]

[tex]3m =15[/tex]

Divide both sides by 3:

[tex]\frac{3m}{3}=\frac{15}{3}[/tex]

[tex]m = 5[/tex]

Therefore, the answer for this equation is [tex]m = 5[/tex].